2018
DOI: 10.4066/biomedicalresearch.61-18-418
|View full text |Cite
|
Sign up to set email alerts
|

Computer-related health problems among university students in Majmaah region, Saudi Arabia

Abstract: Introduction: The increased reliance on computer results in crucial health issues among the users. This research aimed to study the prevalence and factors associated with Computer-related health problems among University students in Majmaah region, Saudi Arabia. Materials and methods: 146 students were selected for this cross-sectional study using conveniencesampling technique. Data regarding personal characteristics, computer usage and prevalence of Musculoskeletal disorders (MSDs), Visual symptoms and sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 32 publications
3
37
0
2
Order By: Relevance
“…Spending many hours using a computer without a break can cause negative effects on users' health.Excessive computer use can lead tomuscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain [10] [19]. Also, a study by [14] as cited in [18] reported that staring at a bright screen for hours can causeeye fatigue or eye strain, headaches, blurred vision, burning, itching or tearing eyes, and temporary vision disorders. [17] found that high prevalence related problems of vision wasprominent among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Spending many hours using a computer without a break can cause negative effects on users' health.Excessive computer use can lead tomuscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain [10] [19]. Also, a study by [14] as cited in [18] reported that staring at a bright screen for hours can causeeye fatigue or eye strain, headaches, blurred vision, burning, itching or tearing eyes, and temporary vision disorders. [17] found that high prevalence related problems of vision wasprominent among university students.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence indicates that a bidirectional relationship exists between psychosomatic conditions and insomnia and that this relationship may be exacerbated by excessive computer use [12][13][14]. The psychological and physical effects of insomnia have secondary consequences for the social and employment stability of affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Pada kuesioner Nordic Body Map berdasarkan [13], skor yang digunakan tingkat keluhan mulai dari agak sakit yang berarti dirasakan sedikit adanya keluhan atau kenyerian pada bagian otot, tetapi belum mengganggu pekerjaan, sakit yang berarti responden merasakan adanya keluhan/kenyerian atau sakit pada bagian otot dan sudah mengganggu pekerjaan, tetapi rasa kenyerian segera hilang setelah dilakukan istirahat dari pekerjaan dan sangat sakit yang berarti responden merasakan keluhan sangat sakit atau sangat nyeri pada bagian otot dan kenyerian tidak segera hilang meskipun telah beristirahat yang lama atau bahkan diperlukan obat pereda nyeri otot [12].…”
Section: Metodologi Penelitian Pengumpulan Data Dilakukan Melalui Survei Secara Daring Terhadap Mahasiswa DI Tiga Program Studi Yaitu Prounclassified
“…Masalah kesehatan mata yang mungkin disebabkan oleh penggunaan perangkat seluler pintar yang intens mungkin tidak terbatas pada masalah permukaan mata seperti mata kering dan disfungsi air mata, tetapi juga dapat mempengaruhi jaringan saraf retina. Penggunaan komputer setiap hari selama 3 jam juga dapat menyebabkan risiko keluhan visual yang semakin meningkat [13].…”
Section: Pembahasan a Kelelahan Mataunclassified